Measurement of distributed dynamic rail strains using a Rayleigh backscatter based fiber optic sensor: Lab and field evaluation. (March 2018) - Wheeler, Lisa N.; Pannese, Eric; Hoult, Neil A.; Take, W. Andy; Le, Hoat
Abstract: Distributed dynamic fiber optic sensors have the potential to measure the strain increase along a rail when it is loaded. This study investigated the use of fiber optic sensors to measure distributed dynamic strains during the passage of rail traffic. The experimental program included both a laboratory evaluation and a field trial. In the laboratory experiments, two methods of affixing the fiber to the rail are compared (minimal and optimal surface preparation) in order to determine whether rapid field installation is possible. Furthermore, displacement measurements from linear potentiometers and Digital Image Correlation are used to illustrate and evaluate the calculation of rail displacement from rail strains. Finally, the distributed strain measurement technique was used to measure rail strains at a level-crossing using vehicular loading under low vibration conditions (hi-rail vehicle) and high vibration conditions (in-service passenger train) to investigate the range of applicability of the current state of this technology under field conditions.